Citizen Engagement in Smart City Planning: The Case of Living Labs in South Korea - Choo, Mijin (2023)
The smart city is recognized as a new city model for inclusive urban planning. Many local governments are making smart city plans to develop new policies that manage urban issues in South Korea. They identify issues through citizen surveys and decide which issues should be managed with priority. Some governments test developed policies based on citizen engagement. Most local governments use the living labs to encourage citizen engagement in smart city plans since these are public spaces where planners engage citizens to develop innovative and inclusive ideas. This study conducted a content analysis of smart city plans of local government. We analyzed the various approaches to the living lab and examined the stage of the planning process it is utilized in. Additionally, we identified the barrier to the living lab by interviewing people who participated in the smart city plan. According to the analysis, a barrier to citizen engagement exists in smart city plans; most citizen engagement is only used when planners develop ideas for setting visions and goals. It implies that citizen engagement occurs at a limited level in smart city plans and may cause planning to be less inclusive. We suggest that citizen engagement should be considered in the whole planning process to improve the inclusiveness of smart city plans and encourage sustainable citizen engagement.